Antara Ikan Garopa dan Otonomi Daerah: Politik Manajemen Sumberdaya Laut - Dedi Adhuri (Antropologi Indonesia, 2001)
There are two arguments that have led scholars and politicians turning their attention into local autonomy issues concerning current discourse and practice of the political resource management systems in Indonesia. Firstly, it is argued that the authoritarian and centralized political and resource management systems of the New Order regime has led Indonesia to a multi crisis situation. Secondly, one of the main strategies coping with this problem is to give local autonomy to the local government and communities to develop their own ways to organize their political and resource management systems. This article challenges the arguments. Two cases of conflict concerning Grouper fishing business-using a symbolic interactionism approach-the author argues that even in the New Order era, there are some indications that local elites, and even ordinary members of the communities, practiced some sort of local autonomy. The discussed cases show that local elites and communities, with power in their hands, will not always develop an effective, just, and sustainable political and resource management systems.